Reversal of Increase in Intestinal Permeability by Mangifera indica Seed Kernel Extract in High-Fat Diet-Induced Obese Mice - Pavan Kumar Mujawdiya; Pravesh Sharma; Shashwat Sharad; Suman Kapur (MDPI AG, 2020)
Obesity and hyper-intestinal permeability are interconnected. This study is designed to evaluate the ability of Mangifera indica seed kernel extract (MESK) in restoring the intestinal barrier and preventing obesity and associated metabolic complications in a high-fat diet-induced obese mouse model. Four groups of Swiss albino mice: (1) normal diet (ND), (2) high-fat diet (HFD), (3) HFD + Orlistat (100 µg/kg), and (4) HFD + MESK (75 µg/kg), were used to monitor various biochemical parameters associated with metabolic syndrome (glucose, total cholesterol, triglycerides) and body weight in an eight-week-long study. In vivo intestinal permeability was determined by the FITC-dextran method. Interestingly, MESK significantly reduced HFD-induced body weight gain, hepatic lipid accumulation, hepatic fibrosis, hyperglycemia, and dyslipidemia. Additionally, MESK treatment restored the expression of tight junction protein Zonula Occludens-1 (ZO-1) and Claudin-1 and hence prevented increased intestinal permeability induced by a high-fat diet. Moreover, it also increased the expression of potent satiety molecule Nesfatin-1 in the mouse jejunum. Our results, for the first time, establish MESK as a nutraceutical which prevents disruption of the intestinal barrier and thereby intercepts the adverse consequences of compromised intestinal permeability such as obesity, hyperglycemia, dyslipidemia, and systemic inflammation.